祁漫塔格造山带——青藏高原北部地壳演化窥探 - 于淼; 丰成友; 何书跃; 赵梦琪; 赵一鸣; 李大新; 瞿泓滢; 刘建楠; 王辉; 周建厚; 钟世华 (地质学报, 2017)
祁漫塔格是东昆仑造山带的一个分支,位于青藏高原中北部,夹持于柴达木盆地和库木库里盆地中间,向西被阿尔金走滑断裂错段.从元古代到早中生代,由于受到多期、多阶段大洋俯冲和关闭影响,导致不同地体间发生碰撞拼贴和大陆增生过程,并由此引发一系列的岩浆事件.祁漫塔格造山带内发育新元古代花岗岩(1000～820Ma)是对Rodinia超大陆形成的响应.以阿达滩和白干湖逆冲断裂为界,划分为南、北祁漫塔格两地体.北祁漫塔格地体作为活动大陆边缘,发育大量的早古生代与俯冲有关的花岗岩和VA型蛇绿岩;南祁漫塔格地体最初为洋内俯冲形成的原始大洋岛弧,发育早古生代SSZ型蛇绿岩、岛弧拉斑玄武岩和钙碱性火山岩.随着持续俯冲,年轻岛弧伴伴随地壳加厚转变为成熟岛弧.南、北祁漫塔格地体间的碰撞(弧—陆碰撞)可能发生在晚志留世(422Ma),并持续到早泥盆世(398Ma).在此期间(422～389Ma),南祁漫塔格地体内发育一系列同碰撞型花岗岩;北祁漫塔格地体内发育一系列的大洋岛弧花岗岩.南祁漫塔格作为外来地体,碰撞拼贴对于大陆边缘、大陆增生意义重大.之后,南、北祁漫塔格地体进入后碰撞环境并发育一系列板内花岗岩.此外,伸展导致造山带垮塌,发育中泥盆统磨拉石建造.碰撞使得海沟后退,海沟阻塞导致俯冲减弱甚至停止,因而产生了石炭—二叠纪(357～251 Ma)岩浆活动缺口.古特提斯祁漫塔格洋的最终关闭可能始于晚二叠世,使得库木库里微板块拼贴于大陆边缘;碰撞抬升导致缺失上二叠统—中三叠统地层.早中三叠世(251～237 Ma)由于碰撞,俯冲大洋板片回转,之后断离,软流圈地幔物质沿岩石圈地幔通道上涌,使得新生下地壳部分熔融;到了晚三叠世,大规模岩石圈地幔和下地壳物质拆沉,导致古老地壳物质发生熔融,形成了一系列后碰撞背景下的钙碱性和碱性花岗岩. The Qiman Tagh Orogenic Belt (QTOB),located along the northern part of the largest Qinghai-Tibet plateau,was constructed through protracted accretion and collision of a collage of terranes during subduction and closure of theQiman Tagh Ocean,a branch of Paleo-Tethys Ocean from the Neoproterozoic to Early Mesozoic.The orogen is located between the Qaidam Basin and Kumukuri Basin,and cut by the Altun Fault to the west.The Early Neoproterozoic (ca.1000～820 Ma) ages from this orogen suggest link with the formation of Rodinia supercontinent.The QTOB is tectonically divided into the North Qiman Tagh Terrane (NQT) and the South Qiman Tagh Terrane (SQT).The NQT developed as an active continental margin,and preserves abundant Early Paleozoic granitoids which possibly formed through the melting of old basement,and a series of mafic-ultramafic rocks considered as VA type ophiolites.In contrast,the SQT witnessed intra-oceanic subduction,where SSZ type ophiolites are documented together with island arc tholeiite (IAT) to the youngest calc-alkaline lavas,in a primary oceanic island arc environment during the Early Paleozoic.With continued subduction,the young island arc was transformed into a mature island arc with thickened crust.This region preserves typical evidence for sedimentation and volcanism in the initial stages of volcanic arc development.The collision between the SQT and NQT occurred probably in the Late Silurian (ca.422 Ma) and continued until ca.398 Ma,as evidenced from the abundant within-plate granites developed in the NQT after 398 Ma.In the SQT,voluminous oceanic island arc granitoids formed during the Early-Middle Devonian (ca.418～389 Ma),with contrasting geochemical features as to those in the NQT.The SQT as an exotic terrane that has been incorporated into the continental margin contributed significantly to the continental growth in this orogenic belt.A trench jam might explain the large gap (ca.357 ～ 251 Ma) of granitoid magmatism.The final closure of thePaleo Tethyan Qiman Tagh Ocean might have occurred in the Late Permian,and resulted in the accretion of the Kumukuri microcontinent.A series of Y-depleted granitoids formed during Early-Middle Triassic (before 237 Ma),which might be associated to the partial melting of thickened lower crust induced by the oceanic lithosphere delamination.Subsequently,a series of calc-alkaline and alkaline granitoids yielded by the old crust melting were emplaced in the SQT,and their formation is linked to the transition from post-collision to within-plate settings. 国土资源部公益性行业科研专项经费项目; 中国地质调查局地质调查项目; 中国地质调查局高层次地质人才培养计划; 青年地质英才计划( 4 703-723 91